Impacts of digitalization and societal changes on energy transition: a novel socio-techno-economic energy system model - L. Stermieri; T. Kober; R. McKenna; T.J. Schmidt; E. Panos (Energy Strategy Reviews, 2023)
The increased diffusion of information and communication technologies (ICTs) impacts daily life and economic growth. It introduces new social practices for households and business models for companies that influence society and energy infrastructure development. A framework capable of quantifying and analyzing the impact of digitalization on achieving energy and climate targets, with a focus on behavioral changes induced by ICT, is currently lacking. In this paper, a new framework is developed that is technology-rich and captures the preferences and behaviors of households and firms in the energy system to assess sustainable energy system configurations that are technically and socially feasible. The framework is designed and demonstrated for Switzerland. We find, for example, that teleworking in Switzerland reduces commuting demand by 10%, and the savings in transport expenses can favor the investment in efficient and clean residential technologies to compensate for the increased residential energy demand due to working at home. This manuscript contributes to the growing literature of suitable frameworks and case studies to account for the co-evolution of society and energy systems in achieving the transition to low-carbon economies.